Enfermedades cardiovasculares y mortalidad hospitalaria por COVID-19 en establecimientos de salud del departamento de Cajamarca, año 2020 - Ninatanta-Ortiz, Juana Aurelia (2024)
Introduction. Cardiovascular diseases are one of the most frequently reported comorbidities in COVID-19 cases. Objective. To evaluate the relationship between the presence of cardiovascular risk diseases and death from COVID-19 in a cohort of hospitalized patients in the Cajamarca Region, during the year 2020. Methods. Retrospective cohort of 576 patients hospitalized for COVID-19 between July and December 2020, from four hospitals in the Cajamarca Region. A survival analysis was carried out using Cox regression to establish the relationship between death from COVID-19 and the presence of arterial hypertension (HTA), type 2 diabetes, obesity, and multimorbidity, using models adjusted for sociodemographic and clinical factors seeking to identify possible effect modifying variables. Results. The mortality from COVID-19 was 45.1%. In the bivariate analysis, the history of HTA was the only cardiovascular disease that was related to a higher probability of death from COVID-19 (HR: 1.43; 95% CI: 1.12-1.85). Two subgroup evaluations were developed:a) by age group and b) by oxygen saturation on admission (SatO2). An association was found between death from COVID-19 and DM2 in those under 60 years of age (HR: 4.56; 95% CI: 2.32-8.95); as well as with HTA in patients with SatO2 less than 80% on admission (HR: 1.67; 95% CI: 1.04-2.69). Conclusion. A relationship was found between death from COVID-19 and cardiovascular diseases such as HTA or type 2 diabetes, in specific subgroups (patients with SatO2 less than 80% on admission or age less than 60 years respectively) of patients who were hospitalized in health establishments of the Cajamarca Region.